2020
DOI: 10.1016/j.swevo.2019.100629
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective adaptive evolutionary algorithm to extract communities in networks

Abstract: Community structure is one of the most important attributes of complex networks, which reveals the hidden rules and behavior characteristics of complex networks. Existing works need to pre-set weight parameters to control the different emphasis on the objective function, and cannot automatically identify the number of communities. In the process of optimization, there will be some challenges, such as premature and inefficiency. This paper presents a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…In addition to verifying the effectiveness of the DDRL-NRA algorithm, we verify the flexibility of the algorithm by changing the resource requirements of end user function requests. Specifically, we adjust the storage resource requirements of the initial end user function requests to [1,20], [1,10], and then conduct experiments from three aspects: resource allocation revenue, end user request acceptance rate and revenue rate. Finally, we also show the comparison of the joint optimization results under three different storage resource requirements.…”
Section: Results and Analysis 1) Training Performance Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to verifying the effectiveness of the DDRL-NRA algorithm, we verify the flexibility of the algorithm by changing the resource requirements of end user function requests. Specifically, we adjust the storage resource requirements of the initial end user function requests to [1,20], [1,10], and then conduct experiments from three aspects: resource allocation revenue, end user request acceptance rate and revenue rate. Finally, we also show the comparison of the joint optimization results under three different storage resource requirements.…”
Section: Results and Analysis 1) Training Performance Verificationmentioning
confidence: 99%
“…Dynamic and intelligent physical network resource management is one of the core businesses of SAGIN [15], [16]. Physical network resource management methods based on heuristic or offline algorithms, such as particle swarm algorithm [17], simulated annealing algorithm [18], genetic algorithm, etc., have all played an active role in physical network resource allocation [19], [20]. It cannot be ignored that the above algorithms have many limitations in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…From the experimental and simulation studies on real life networks, the proposed model was found more effective than the state-of-the-art approaches, including those proposed by [20] and [41]. Recently, several studies were published based the work of Amelio and Pizzuti, such as those of Sani et al [47], and Li et al [48]. Attea et al [49] focused on CD problem reformulation as a MOO model for simultaneous detection of intra-and inter-community structures; a heuristic perturbation operator was also suggested for emphasizing the detection of the intra-and inter-community connections in order to establish a positive relation with the MOO model, which is given as follows:…”
Section: A Community Detection: Historical Overviewmentioning
confidence: 93%
“…For the guided matting results in Fig. 2, the images are enhanced firstly [32][33], then they are segmented by using the improved graph-based, the region merging [27,34] based mean-shift model [35] and edge detection [36][37] algorithms respectively. The experimental results are shown in Fig.…”
Section: Fine-segmentation On Graph-based Algorithm and Comparing Wit...mentioning
confidence: 99%